Respuesta :

Check the picture below.

Ver imagen jdoe0001
Let me explain this in 2 parts as it may be hard to understand if it's explained all at once.

x(squared)= 9(squarded) - 5(squared)

So that is 9x9=81, and 5x5=25.

81+25= 106

So then... 106= X(squared)

106(square root)

10.3=x

Part 2 is the second triangle.

y(squared)= 5(squared) + 3(squared)

So that's 5x5= 25 and 3x3= 9.
25+9= 34

So then... 34= Y(squared)

34(square root)

5.8=y

Final Answers are....

X= 10.3
Y= 5.8

Hope this helped. :)